How do Australian ICU survivors fare functionally 6 months after admission? - Dennis, D.; Hebden-Todd, T.; Marsh, L.; Cipriano, L.; Parsons, Richard (Australasian Academy of Critical Care Medicine, 2011)
Objectives: To determine the extent to which physical function is restored 6 months after intensive care unit admission, and whether this is associated with short or long ICU length of stay (LOS). Design, setting and participants: We conducted a prospective observational study between April and June 2010. All patients admitted for more than 48 hours to the general ICU at Sir Charles Gairdner Hospital, Perth, Western Australia, were eligible for inclusion. "Short" and "long" ICU LOS were defined as < 8 days and > 8 days, respectively. Six months after ICU admission, an investigator (blinded to baseline data) contacted participants by telephone to administer a follow-up questionnaire based on the Functional Independence Measure (FIM). Outcome measures: The primary measure was FIM score; secondary measures were rehabilitation requirement, readmission rate, and whether or not patients had returned to work and driving.Results: 77 patients consented to take part in the study, and 71 were followed up. Median total FIM score (124) and motor (89) and cognitive (35) subscores suggested high-level functional independence at follow-up. Fifty per cent of patients who were workers at baseline had returned to work, and 76% of drivers had returned to driving at follow-up. Paired t tests of the changes in total FIM and its subscales showed that only the motor subscore showed a significant deterioration (mean change, -3.7; P=0.04). Changes for the total FIM did not appear to be correlated with any demographic or baseline data. Furthermore, there appeared to be no difference in FIM between patients with short or long ICU LOS. Conclusions: Our study showed that patients who survive treatment for life-threatening illness in an Australian ICU for more than 48 hours and are subsequently able to communicate are likely to return to their premorbid functional level (as defined by FIM score within 6 months).